Menerapkan Pelaporan Terpadu untuk Mengungkapkan Modal Intelektual di Perguruan Tinggi - Rachmawati, Rima; Sari, Diana; F. Rodelas, Allan Nicko (Politeknik Ganesha Medan, 2024)
This research aims to provide empirical and theoretical solutions to certain criticalities in the Integrated Implementation Reporting framework (IIRF) in the context of higher education. Indeed, IIRF considers value creation only from the perspective of capital gains driven by academic activities, neglecting the fulfilment of the institutional mission as a true lever of value creation. This paper introduces a case study that aims to implement IIRF in an Indonesian university. The research is based on theory development from case, action research, and intervention approaches. IIRF was chosen for its claimed ability to support the process of communication with stakeholders and control over value creation, despite some weaknesses. This research highlights the role played by intellectual capital in an organisation's business model and in the value creation process. This adjustment seems to raise awareness of the role of intellectual capital in value creation in universities. In this paper, no single part of the adapted framework is innovative in isolation, but collectively they provide an innovative solution, which addresses the disclosures and managerial needs of the organisation under study. This single case study allowed us to test the IIRF's weaknesses claimed in the literature, suggest some adjustments to the original framework, and validate its effectiveness. Thanks to the single case study, we were then able to build a theoretical framework that develops theory inductively; now the suggested framework can be further tested and validated in other organisations. This paper introduces an innovative approach to reporting and disclosing intellectual capital in universities. This approach is relevant not only for external communication but also for internal purposes, assisting managers in decision-making and action